Uterine leiomyosarcoma: an unusual presentation - B., Preethi; Singh, Monu; Singh, Sarita; Singh, Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Uterine leiomyosarcomas are rare aggressive tumors, with high recurrence rates, even when confined to the uterine corpus at the time of diagnosis. It arises from smooth muscle of uterus and is a rare tumor that accounts for 2-5% of all uterine malignancies. These tumors typically spread hematogenously. Patients present with vague symptoms similar to those of patients with leiomyomas. Most patients are diagnosed with leiomyosarcoma postoperatively. Although prognosis remains dismal, various ongoing studies are investigating the role of advanced imaging, multimodality treatment, prognostic nomograms, and unique biomedical pathways to increase understanding of leiomyosarcoma and improve therapeutic options for patients. 46 years old para2 live2 postmenopausal (since 1.5 year) female presented to outpatient clinic with complaints of bleeding per vaginum, foul smelling discharge, unquantified weight loss and something coming out of vagina since 1.5 months. On abdominal examination, an irregular midline mass arising from pelvis corresponding to 20 weeks gestational size of uterus was present. On vaginal examination, 3 infected vaginal growths were present in vagina maximum 4x4cm. Intra-operatively, uterus was nearly 20 weeks size with irregular surface. A 3×3 cm subseroal fibroid with necrotic surface was present on posterior wall of uterus. Cut section of the operative specimen showed myohyperplasia which was compressing the uterine cavity, some necrotic areas were also present. Vaginal growths - 4×4 cm on left vaginal wall near introitus with necrotic surface, 3×3 cm on right vaginal wall, 1×1 cm on right upper vaginal wall present. Excision of vaginal growth was done and was sent for histopathology. Histopathologic examination of sections of uterus showed all features were suggestive of leiomyosarcoma uterus.